Aromatase cytochrome P450 enzyme expression in human pituitary - (:unkn) unknown (SPRINGER, 2008)
Aromatase (P450AROM) converts testosterone to estrogen. This conversion could be important in normal physiology and estradiol-induced tumorigenesis in human pituitary. The objective of this study was to examine the expression of P450AROM in normal human pituitary and determine the gender difference. We examined aromatase expression in 19 normal human pituitary glands [13 males, 6 females, median age: 30 years (interquartile ranges, IQR: 23-63)] obtained from autopsy. We demonstrated aromatase gene expression levels by quantitative RT-PCR and aromatase protein with immunohistochemical staining in normal male and female human pituitary. Although median relative expression level of aromatase mRNA of male individuals [median Delta Ct = 42.6 (IQR: 7.6-93.9)] was higher than the female individuals [median Delta Ct = 3.9 (IQR:0-44.8)], we could not determine a significant gender difference in aromatase mRNA levels (p = 0.2). The difference between the aromatase protein density by immunohistochemistry was not significant between genders (p = 0.78). The aromatase levels were also not correlated with the age of the study subjects (p = 0.42 r = -0.21). The results indicate that aromatase enzyme is present in human pituitary. The amount and the density of the enzyme show a large variance among different individuals. Although higher mRNA expression was observed in male pituitary compared to female pituitary, there was no statistically significant difference for gender or age.
Keywords: testosterone; aromatase expression; pituitary; human; ENCODING HUMAN AROMATASE; GONADOTROPIN-SECRETION; RAT-BRAIN; TESTOSTERONE; ESTROGEN; PROLACTINOMA; ESTRADIOL; P450